2019
DOI: 10.1016/j.jmmm.2019.165620
|View full text |Cite
|
Sign up to set email alerts
|

Electron doping induced magnetic glassy state in phase separated YBaCo2O5.5-δ

Abstract: The structural, magnetic and transport properties of the layered RBaCo2O5.5±δ cobaltites are sensitive to the oxygen stoichiometry. In this present study, we report the presence of a low-temperature magnetic glassy state in electrondoped polycrystalline YBaCo2O5.5 cobaltite. The ac magnetization studies show the absence of conventional spin glass features, while the various dc magnetization studies demonstrate the presence of non-equilibrium magnetic glassy state at low temperature. The magnetic glassy state o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…On the other hand, the formation of MG is also reported in the layered YBaCo 2 O 5+δ (δ = 0.50) cobaltite with 5% Ca substitution at Y and Ba sites [10]. In complement to the Ca substitution studies, we have shown that the electron doped YBaCo 2 O 5.5−δ (δ = 0.13) cobaltite also showed the presence of MG state at low temperature (T) [17]. However, magneto structural coupling hardly plays a role in both the cobaltites and the MG phenomenon is explained considering the local phase separation of FM and AFM clusters.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…On the other hand, the formation of MG is also reported in the layered YBaCo 2 O 5+δ (δ = 0.50) cobaltite with 5% Ca substitution at Y and Ba sites [10]. In complement to the Ca substitution studies, we have shown that the electron doped YBaCo 2 O 5.5−δ (δ = 0.13) cobaltite also showed the presence of MG state at low temperature (T) [17]. However, magneto structural coupling hardly plays a role in both the cobaltites and the MG phenomenon is explained considering the local phase separation of FM and AFM clusters.…”
Section: Introductionsupporting
confidence: 59%
“…Finally, it is worth to compare the MG state of the present EBCO with the other available reports of this cobaltite family. The MG state is reported in the YBaCo2O5+δ (δ = 0.50) cobaltite with 5% Ca substitution at Y and Ba sites [10] and also in the electron doped YBaCo2O5.5-δ (δ = 0.13) [18] , where the arrested phase has very low magnetization. The isothermal magnetic entropy studies also show the large entropy change at the kinetically arrested phase.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
See 1 more Smart Citation